Calculation of natural radiation transfer factors in some agricultural crops in Al-Hussainiya- Karbala -Iraq - Heiyam Najy Hady, Zainab Shakir Baqer (Scientific Trends, 2023)
To study the radiation transfer factor TFs of agricultural crops in the Al-Hussainiya area - Karbala, Iraq. an amount of 30 sample has been collected from different locations (randomly distribution ) of the Al-Hussainiya area, including (15plant samples and 15 soil samples) for three samples of agricultural crops (Eggplant, Okra, Common pea). The natural radioactivity of the (_^238)U, (_^232)Th and (_^40)K isotopes were measured by a gamma-ray spectroscopy with scintillation detector NaI (TI) 〖(3〗^''×3^'') from ORTEC with an efficiency of (4.6) at energy (662 keV) and energy resolution (7.9)%. The specific activity of (_^238)U, (_^232)Th and(_^40)K, have been measured, in which radiation Transfer Factor TF of (_^238)U, (_^232)Th and(_^40)K, The radium equivalent Ra_eq, gamma radiation reprehensive level index I_γ, external hazard index H_ex and internal hazard index H_in all have been measured. It was found that the highest rate of the(_^238)U specific activity was in the Okra plant sample, where it reached 17.896±2.020 Bq.kg^(-1), and the sample of the soil was 24.520±1.563 Bq.kg^(-1). The specific activity of (_^232)Th in the common pea plant sample was 10.959 ± 1.519 Bq.kg^(-1) while the soil sample was 12.86±0.944 Bq.kg^(-1). The specific activity of (_^40)K in the eggplant plant sample reached to 274.583 ±7.583 Bq.kg^(-1) and in soil sample was 324.40±15.811 Bq.kg^(-1). Radiation Transfer Factor TF of (_^238)U was the highest rate in the eggplant samples, in which it reached 0.885, (_^232)Th TF was the highest in the common pea samples, which reached 0.847, and (_^40)K TF was the highest rate in the eggplant samples where it was 0.855.The radium equivalent Ra_eq, where the highest rate for the plant in the common pea samples it was 48.856 Bq.kg^(-1). The gamma radiation reprehensive level index I_γ was the highest rate for the plant in the common pea samples; it was 0.369 Bq.kg^(-1). The external hazard index H_ex was the highest rate for the plant in the common pea sample 0.131 Bq.kg^(-1) while for the Internal hazard index H_in the highest rate was in the okra plant sample where it was 0.180 Bq.kg^(-1). The obtained results for the selected samples were within the acceptable worldwide limit. The radiation transfer factor TFs for the three types of plants was almost the same